Penyelesaian Wanprestasi pada Perjanjian Jual Belisarana Produksi Pertanian (Saprodi) antara CV Karya Tani dengan Toko Riska Tani - Nurfauzia, Nurfauzia (Universitas Batanghari Jambi, 2018)
Default is where one of the parties has committed an act that is not in accordance with the rights and obligations that they have agreed to or in other words the lack of implementation of the promise. accounts payable to CV Karya Tani in the form of agricultural materials such as fertilizers, seeds and medicine for poison grass with a debt of Rp. 270,000,000 (two hundred seventy million rupiahs) with a period of 30 days will be returned to CV Karya Tani but Riska Farmer's shop has defaulted. The approach method used in this research is sociological juridical namely the approach that is carried out by legal reality in practice. the settlement made by CV Karya Tani for Karya Tani Shop to immediately pay for shortages when purchasing inputs, namely having 3 efforts namely Consensus Meeting, Making a Statement, Settlement through the Jambi District Court, Sita guarantee